FUNGSI PEMERINTAH DAERAH DALAM PEMBERDAYAAN INDUSTRI KERAJINAN ROTAN DI KOTA PEKANBARU TAHUN 2012-2015 - Yohandes, Berlin Oktaviani; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The development of rattan craft is growing rapidly in Pekanbaru City with the result of the works in the form of various forms of interesting creations so much to the outside of Pekanbaru, even already exported to neighboring countries namely Malaysia and Singapore, but according to the Office of Industry and Trade Pekanbaru City since 2009 until 2015 Rattan Craft Industry in Pekanbaru City only amounted to 11 industries. The data explains that Formal Rattan Industry has not improved since 2009. The purpose of this research is to know the function of local government in empowering rattan handicraft industry in Pekanbaru City year 2012-2015 and to know the factors that hamper the function of local government in empowering rattan craft industry in Pekanbaru City in 2012-2015.The research method used is survey research. The location of this research is in Pekanbaru City which is the capital of Riau Province. Pekanbaru City currently has a rapid development in the field of rattan crafts with the work of various forms of creation that attracted so much to the outside of Pekanbaru.The results of research on the function of local government in empowering rattan handicraft industry in Pekanbaru City in 2012-2015, on enabling indicators of Riau Provincial Government has built central rattan and continue to promote rattan craft industry in Pekanbaru city in various activities such as at certain events. There is no investor interest in Rattan Craft Industry in Pekanbaru City. In empowering indicators of Riau Provincial Government to strengthen the provision of misplaced facilities KUR (People's Business Credit) but hindered on loan guarantees. In Protecting indicators Local Government of Riau Province has not been able to overcome the problem of rattan raw material scarcity for rattan craft industry in Pekanbaru City.Keywords: Functions of Government, Empowerment, Department of Industry and Trade Pekanbaru City.